Global issues in corporate law - Gevurtz, Franklin (St. Paul, MN : Thomson/West, 2006)
"This book is designed ... as a supplement ... to introduce ... students to corporate outside of the United States."--Preface, p. v.
Includes bibliographical references and index.
Keywords: Corporation law; International business enterprises -- Law and legislation; Globalization